Safety profile of successful treatment of hormonal disorders in gynecology - P. V. Budanov; A. A. Churganova; A. G. Aslanov; T. I. Shubina (Медицинский совет, 2015)
Menstrual dysfunction and preparing for pregnancy require safe prevention and careful support of the reproductive function. Cyclic vitamin therapy meets the requirements, while Time-factor, the vitamin and mineral supplement, is characterized by high compliance and convenience of use. For a pre- or postmenopausal patient, Estrovel with phytoestrogens combines high safety profile and the possibility for self-selection with adequate tolerance and the possibility for prolonged use.